Access to online databases at private colleges and universities in Malaysia - Teow, P.L.; Zainab, A.N. (2003)
Describes a survey of 26 libraries at private colleges and universities (PCU) in Malaysia to ascertain the types of access given to online databases. The PCUs include (a) private colleges that offer franchised undergraduate programmes in collaboration with foreign universities; (b) institutions that are branch campuses of foreign universities; and (c) Malaysian-based PCUs that are owned by Malaysian corporations. Out of the 26 PCUs, only 8 out of 19 colleges and 7 local private universities and foreign branch campuses provide access to online databases to their students. The types of access given are: (a) the private universities provide access to online databases that they subscribe through their own funding and control usage through a mixture of user name/password and IP-based access; (b) the foreign universities with branch campuses in Malaysia provide access by three modes (online databases subscribed from branch campusâs own funding; online databases subscribed by foreign partner university; online databases subscribed by local branch campus own funding as well as those subscribed by the foreign partner university). Almost all PCUs provide their undergraduates with computer facilities to access the databases. A variety of methods are used to promote usage, which include library induction, library brochures, library notices and providing links through the libraryâs own web pages. Most PCUs do not charge for access and provide users with the option to print, download or receive documents.